Growth of Indian Life Insurance Density and Penetration - Prasad, R Sivarama; NSharma, R S (Ushus Journal of Business Management, 2017)
The Government of India nationalized insurance industry in 1956 on 19th Januaryleading to the amalgamation of154 Indian, 16 non-Indian Insurers and 75 provident societies, in total 245 Indian and foreign insurers, to form the Life Insurance Corporation of India. The Life Insurance Corporation of India, a public sector corporation, enjoyeda monopoly in the business for four decades until the entry of private life insurers with foreign joint ventures having 26% Foreign Direct Investment(FDI).As per one of the major recommendations of Sri R N Malhotra committee, on 19th April 2000, Insurance Regulatory and Development Authority was set up by the Government of India through the passing of an act of the Parliament. The IRDA aimed to promote insurance and protect the insured. Since its formation, the IRDA has been proving itself successful in promoting orderly growth and development in Indian Insurance sector. This study is an attempt to study life insurance density and penetration in Indian life Insurance industry toassess the growth in theexpansion of life insurance business in India. An analysisis made, and some conclusions are drawn with the help of growth percentages and trend calculations